PENGEMBANGAN KOMIK SEBAGAI MEDIA PEMBELAJARAN IPA DI KELAS 5 SD NEGERI 37 PEKANBARU - Riri Indriana; Mahmud Alpusari; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The use of instructional media will greatly assist the effectiveness of the learning process and the delivery of learning materials. The purpose of this study was to develop and assess the feasibility of comics as a medium of learning science in elementary grades in the subject land. This reaserch was conducted at Departement of Education Elementary School Teacher University of Riau and SDN 37 Pekanbaru.This type of research is the development of research using ADDIE models of design research, but limited to the development phase. The instrument used to collect data is a validation of the feasibility sheet comics as a medium of learning consisting of 26 reports have been completed by 5 validator. Furthermore, the trial is limited to 37 elementary students in the form of questions and the questionnaire responses of students who performed at the SD Negeri 37 Pekanbaru. The data is then analyzed using descriptive analysis. The tests the feasibility of developing a comic can be seen from five aspects: simplicity, emphasis, balance, alignment and design of the comic. Overall results validate the feasibility of the comic gets a percentage 89.80% categorized as very feasible. The test result is a finite limit to the effectiveness of the media to see an increase of 0.69 gain medium category and the students' response to the comics is excellent with an average percentage of 86.75%.Keywords: Comics, Media Education, Development Research.